Perceived seriousness dan kepatuhan pada pasien diabetes melitus tipe 2: Psychological distress sebagai moderator: Perceived seriousness and compliance in patients with type 2 diabetes mellitus: Psychological distress as a moderator - Hendrati, Theresia Mustika Wahyu; Asih, Sali Rahadi (Persona:Jurnal Psikologi Indonesia, 2024)
Type 2 diabetes mellitus is a chronic disease with a high global prevalence, so efforts to reduce the prevalence of this disease are needed. This study aims to evaluate the role of psychological distress as a moderator in the relationship between perceived seriousness and adherence to diabetes management. A total of 107 type 2 diabetes patients aged 26-82 years participated in this study, with a percentage of women of 74.8%. This study is a cross-sectional study with a correlational research type that will measure the relationship between three variables, namely psychological distress, perceived threat, and adherence to diabetes management. The measuring instruments used are Perceived Seriousness, General Health Questionnaire-12, and Diabetes Activity Questionnaire. Data were processed using regression techniques with PROCESS v4.0 to see the moderation relationship between variables. The results of the moderation analysis showed that psychological stress significantly moderated the relationship between perceived seriousness and adherence. This study found that higher psychological distress was associated with a weaker relationship between perceived seriousness and compliance, whereas higher psychological distress strengthened the impact of perceived seriousness on compliance.